Improving Students Learning Result Through Coorperative Type SAVI - Tiadsen Loupatty; Mujasam Mujasam; Sri Rosepda Br. Sebayang (Kasuari: Physics Education Journal (KPEJ), 2019)
This research aims to find out how the application of cooperative model in SAVI type to increase students’ result of learning in the class XI IPA SMA Adventist Manokwari, so that in the process of learning physics, students have a good value and they do not think that physics is a very difficult lesson. The instrument used is an assignment test for cognitive measures and LKPD for psychomotor measures. This research using the Classroom Action Research method (CAR). The results of this research indicate that, in cycle I the total cognitive value of each student 83 with 100% classical completeness, and the total psychomotor value of students 93 with 100% classical completeness. Cycle II the total cognitive value 88 with 100% classical completeness, and the psychomotor 94 with 100% classical completeness. This shows that, learners learn to increase.